CCTV surveillance in primary schools: normalisation, resistance, and children's privacy consciousness. (4th March 2018) - Birnhack, Michael; Perry-Hazan, Lotem; German Ben-Hayun, Shiran
Abstract: This study explored how primary school children perceive school surveillance by Closed Circuit TV systems (CCTVs) and how their perceptions relate to their privacy consciousness. It drew on interviews with 57 children, aged 9–12, who were enrolled in three Israeli public schools that had installed CCTVs, and on information gathered from members of the management team of each school. The findings indicated that in all three schools, educators did not discuss the CCTVs with the children. Consequently, most children had various erroneous assumptions regarding the CCTVs, leading some children to wrongly believe that they were seen and heard in almost every corner of the school, including toilets and classrooms. The findings also revealed a tension between normalisation of school surveillance on the one hand, and resistance to excessive surveillance on the other. In addition, the findings demonstrated that even young children, having been born and raised in a digital world with its ubiquitous surveillance, value their privacy and are willing to relinquish it only when they perceive it as justified. The moral balance voiced by the children regarding the circumstances that justify trading privacy for security resembles constitutional analysis.